Optimization of seed priming to enhance germination and early seedlings growth of rice (Oryza sativa L.) VAR. FARO44 under drought stress - Ali, Lawan Gana (2021)
Priming of seed is a simple physiological approach that enhances germination, seedling growth and imparts drought stress tolerance to germinating seeds and seedlings. Rice is an important staple crop produced and consumed by more than 50% of people worldwide. However, poor germination and irregular seedling emergence in directseeded rice production caused by drought in a changing climate are the major causes of low yield in the tropical countries. In this study, rice seeds var. FARO44 was primed with different chemicals to enhance germination, seedling growth and drought tolerance. The objectives of the study include: (i) evaluate the suitability of potassium nitrate (KNO3), silicon dioxide (SiO2) and salicylic acid (SA) as priming agents for FARO44 rice germination and early seedling growth, (ii) evaluate the effects of seed priming on germination, early seedling growth and biochemical characteristics of rice seedlings under drought conditions, (iii) compare the activities of protective enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) of rice seedlings under drought conditions and (iv) evaluate the effects of seed priming on drought tolerance of FARO44 rice seedlings under drought conditions. In experiment one, rice seeds were primed each with KNO3 (2.5%, 5%, 10%, 15% and 20%), SiO2 (2.5%, 3%, 3.5%, 4% and 4.5%) and SA (0.007%, 0.014%, 0.021%, 0.028% and 0.035%). Primed rice seeds were then germinated in Petri dishes for two weeks. The experiments were arranged in a completely randomized design with each treatment replicated five times. Thereafter, germination percentage (GP), mean germination time (MGT), germination index (GI) and seedling growth were evaluated. In experiment two, rice seeds were primed with optimal concentrations of KNO3 (2.5% and 5% w/v), SiO2 (3% and 3.5%) and SA (0.014% and 0.035%) and their combinations (5% KNO3+3% SiO2; 2.5% KNO3+3.5% SiO2; 0.014% SA+5% KNO3; 0.035% SA+2.5% KNO3; 3% SiO2+0.035% SA; 3.5% SiO2+0.014% SA; 5% KNO3+3% SiO2+0.035% SA and 2.5% KNO3+3.5% KNO3+0.014% SA). Primed rice seeds were then germinated and grown under three osmotic stress conditions of low (-0.3 Mpa), moderate (-0.6 Mpa) and severe (-0.9 Mpa) induced by polyethylene glycol for two weeks. Thereafter, GP, MGT, GI, seedling growth performances, activities of SOD, CAT and APX, total soluble protein, proline, carbohydrate, total chlorophyll, total soluble sugar and malondialdehyde content, and membrane stability were evaluated. In experiment three and four, primed rice seeds with KNO3 (2.5% and 5%), SiO2 (3% and 3.5%) and SA (0.014% and 0.035%) were grown in the net house in plastic pots under well-watered and low, moderate and severe drought conditions for six weeks. Plastic pots were arranged in CRD and replicated five times. Emergence characteristics, seedling growth performances, activities of CAT, APX, SOD, total soluble protein, proline, carbohydrate, total soluble sugar, total chlorophyll and malondialdehyde content, and membrane stability of seedlings were evaluated. In the laboratory studies under well-watered conditions, the results revealed that KNO3, SiO2 and SA priming significantly (P ≤ 0.05) enhanced germination index, shortened germination time and improved seedling growth, seedling biomass and seedling vigour indices of rice seedlings. However, germination percentage was not improved by seed priming. Seed priming with 2.5% and 5% KNO3, 3% and 3.5% SiO2, 0.014% SA and 0.035% SA showed more effects in enhancing germination and seedling growth of FARO44 rice than other concentrations of these chemicals. Likewise, under osmotic stress conditions, 2.5% and 5% KNO3, 3% and 3.5% SiO2, 0.014% SA and 0.035% SA priming significantly (P ≤ 0.05) improved GP, GI, MGT and seedling growth of FARO44 rice more than combined priming with KNO3+SiO2, SiO2+SA, SA+KNO3 and KNO3+SiO2+SA. The results also showed that 2.5% and 5% KNO3, 3% and 3.5% SiO2, 0.014% SA and 0.035% SA priming significantly (P ≤ 0.05) enhanced CAT, APX and SOD activities of rice seedlings by more than 2 folds compared to control. Likewise, seed priming significantly (P ≤ 0.05) improved total soluble protein, total chlorophyll, carbohydrate, soluble sugar and proline content, membrane stability and decreased lipid peroxidation by more than 5-folds in rice seedlings under osmotic stress conditions. Combined priming with KNO3+SiO2, SiO2+SA, SA+KNO3 and KNO3+SiO2+SA showed less effects in enhancing protective activities of CAT, APX and SOD, and total soluble protein, total chlorophyll, carbohydrate, soluble sugar and proline contents of rice seedling under osmotic stress conditions than priming with these chemicals separately. Under both well-watered and drought conditions in the net house, 2.5% and 5% KNO3, 3% and 3.5% SiO2, 0.014% SA and 0.035% SA priming significantly (P ≤ 0.05) enhanced emergence attributes, seedling growth and drought tolerance of FARO44 rice seedlings. However, 2.5% and 5% KNO3, 3% and 3.5% SiO2 priming showed more effects than SA priming. Similarly, the results found that seed priming significantly (P ≤ 0.05) improved total soluble protein content, activities of CAT, APX and SOD, carbohydrate, total soluble protein, soluble sugar, total chlorophyll and proline content and membrane stability, while MDA content decreased by more than 4-folds than control in rice seedlings grown in net house under drought conditions. Thus, the findings of this study established that KNO3 (2.5% and 5%) and SiO2 (3% and 3.5%) priming are effective for fast germination, seedling establishment, seedling growth and for imparting drought tolerance to FARO44 rice grown in tropical ecosystems.